2023
DOI: 10.31219/osf.io/wkhx4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aging as a morphostasis defect: a developmental bioelectricity perspective

Abstract: Maintaining order at the tissue level is crucial throughout the lifespan, as failure can lead to cancer and an accumulation of molecular and cellular disorders. We argue here that the most consistent and pervasive result of these failures is aging, which is characterized by the progressive loss of function and decline in the abilityn to maintain anatomical homeostasis and reproduce. This leads to organ malfunction, diseases, and ultimately death. The traditional understanding of aging is that it is caused by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 290 publications
0
4
0
Order By: Relevance
“…Moreover, by choosing a proper fitness function related to measuring scale-invariant pattern formation 107,143 , critical dynamics [144][145][146][147][148][149] , or applying the free-energy principle 141,150 , we are confident to achieve a biologically more accurate model of the scale-free dynamics and open-ended evolution of life. Such computational models could thus further quantitative studies of the communication strategies and boundaries of individual-and groups of cells in an agential, potentially adversarial Umwelt, with possible applications in individual-and collective aging (as morphostasis defects) 151,152 or cancer research 93,94,136 . number of N FF = 194 parameters (c.f., section III A).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by choosing a proper fitness function related to measuring scale-invariant pattern formation 107,143 , critical dynamics [144][145][146][147][148][149] , or applying the free-energy principle 141,150 , we are confident to achieve a biologically more accurate model of the scale-free dynamics and open-ended evolution of life. Such computational models could thus further quantitative studies of the communication strategies and boundaries of individual-and groups of cells in an agential, potentially adversarial Umwelt, with possible applications in individual-and collective aging (as morphostasis defects) 151,152 or cancer research 93,94,136 . number of N FF = 194 parameters (c.f., section III A).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been suggested that bioelectric networks act as body coordinators, modulating communications between cells and tissue ( Levin, 2023 ). Ageing would then begin following the miscoordination of such signals, leading to divergence and aberrancies in tissue and organ behaviours ( Pio-Lopez and Levin, 2024 ). Could this be linked to the transcriptional noise increase observed with time?…”
Section: Discussionmentioning
confidence: 99%
“…These insights, together with the development of computational models, combined with the repurposing of existing FDA-approved drugs, have great potential to lead to the development of gero-electroceuticals that combat aging, reverse replicative senescence, and bring cancer cell proliferation to a halt by normalizing bioelectric homeostasis (Figure 4). 27,[79][80][81] The non-locality of bioelectric information also offers the possibility of surrogate-site diagnostics and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicin, a TRPV1 agonist, induces axonal growth; and fluoxetine, a serotonin transporter inhibitor, suppresses melanoma. 81 Together, there is a growing optimism that ion channel drugs might be tailored to generate gero-electroceuticals that alleviate aging and age-related disorders.…”
Section: Discussionmentioning
confidence: 99%